Techno-Populism revisited: A Comparison between the Italian Five Stars Movement (Movimento 5 Stelle) and the Chilean People’s Party (Partido de la Gente) - Padoan, Enrico (Política. Revista de Ciencia Política, 2023)
This paper compares the ideological and organizational trajectory of the Italian M5S (Movimento Cinque Stelle) with the ideological and organizational foundations and characteristics of a recently born party, the Chilean Partido de la Gente (PdG). This paper aims not only at putting the early trajectory of the PdG in comparative perspective and to start focusing on an under-researched party. This paper also aims at debating over the analytical strengths and weaknesses of adopting the conceptual lens of ‘technopopulism’ to classify and understand both the M5S and the PdG. This paper argues that these two parties share (more exactly, shared, because of the evolution of the Italian party) not only several genetic discoursive and (to a minor extent) organizational characteristics, but also some (albeit not all) contextual (historical, social, political) conditions favoring their successful emergence and electoral consolidation. At the same time, a closer analysis sheds some lights on important ideological (and, consequently, socio-political, i.e. in terms of class appeals) differences that may contribute to understand their seemingly diverging evolutions. These differences suggest that the concept of ‘techno-populism’, while analytically useful and even attractive, may also obscure strongly different ideological foundations of parties sharing the same techno-populist logic. Contra defenders of the ‘techno-populist’ concept, the traditional left-right dimensions (in our case, mostly declined through the pro-state/pro-market divide) are destined to reappear, sooner or later, in the surface.